Space-time propagation of air pollution from dot source: Quasi 1D model - Stevo K. Jaćimovski; Jelena Lamovec; Jovan P. Šetrajčić (Zaštita Materijala)
The problem of pollution - especially air pollution in big cities, has arisen with rapid technological development. This paper analyzes the propagation of air pollution originating from periodical dot sources. Pollution will be is examined as a quasi-one-dimensional directed from the source, in case when diffusion processes, absorption and airflow occur. The partial differential equation describing all given processes is solved numerically for the adopted real parameters of the mentioned processes. The time change of the concentration of air pollution with distance from its source was determined.